2011
DOI: 10.1139/f2011-019
|View full text |Cite
|
Sign up to set email alerts
|

Capture technique and fish personality: angling targets timid bluegill sunfish,Lepomis macrochirus

Abstract: Size-selective harvesting associated with commercial and recreational fishing practices has been shown to alter life history traits through a phenomenon known as fishing-induced evolution. This phenomenon may be a result of selection pathways targeting life-history traits directly or indirectly through correlations with behavioral traits. Here, we report on the relationship between individual differences in behavior and capture technique (beach seining versus angling) in wild-caught juvenile bluegill sunfish (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
117
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(123 citation statements)
references
References 49 publications
3
117
3
Order By: Relevance
“…consistent behavioural differences among individuals across time and different contexts, have been of high interest among behavioural ecologists during the last decade (Sih et al 2004;Réale et al 2010;Stamps and Groothuis 2010;Mittelbach et al 2014). Recently, they have also received increasing attention in applied contexts, such as among studies on harvesting-induced evolutionary changes (Wilson et al 2011;Binder et al 2012;Härkönen et al 2014). In particular, selective harvesting of certain behavioural types has been predicted to impose fishing-induced selection on fish personality (Lewin et al 2006;Uusi-Heikkilä et al 2008;Conrad et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…consistent behavioural differences among individuals across time and different contexts, have been of high interest among behavioural ecologists during the last decade (Sih et al 2004;Réale et al 2010;Stamps and Groothuis 2010;Mittelbach et al 2014). Recently, they have also received increasing attention in applied contexts, such as among studies on harvesting-induced evolutionary changes (Wilson et al 2011;Binder et al 2012;Härkönen et al 2014). In particular, selective harvesting of certain behavioural types has been predicted to impose fishing-induced selection on fish personality (Lewin et al 2006;Uusi-Heikkilä et al 2008;Conrad et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…More complex exploitation patterns with respect to traits selected by fishing are conceivable for passively operated fishing gears (where the odds of capturing a fish depends on a fish's decision to attack and/or ingest baited hooks), such as recreational angling (Uusi-Heikkilä et al 2008). In many recreational harvesting situations, such as hook-and-line angling, selection of a range of behavioural, physiological and life-history correlated traits is conceivable (Cooke et al 2007, Uusi-Heikkilä et al 2008, Redpath et al 2009, Wilson et al 2011, Sutter et al 2012. The resulting complexity of selection pressures on a range of traits that are correlated with the overarching trait 'vulnerability to fishing' suggests that the selection differentials caused by recreational angling may not necessarily show the expected sign.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has sought to link this risk-taking behavior to angling vulnerability, and results have been inconsistent. Some studies indicate that bolder and more exploratory individuals are more vulnerable to capture by anglers (Härkönen et al, 2014(Härkönen et al, , 2016Klefoth et al, 2013); other work has found bold individuals to be less vulnerable to angling (Wilson et al, 2011); and still other work has found no connection between boldness and angling vulnerability (Kekäläinen et al, 2014;Vainikka et al, 2016). Inconsistent findings linking boldness to angling vulnerability may be due to differences in methodology across studies (Beckmann and Biro, 2013), or may indicate that a relationship between boldness and vulnerability is context dependent and may fluctuate depending on factors such as the species in question or the time of year (for instance, during the spawning season, vulnerability to angling may depend to a greater degree on factors related to aggressiveness; see Sutter et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…For example, previous work has shown that bolder and more active individuals may be more likely to be caught on hookand-line gear (Härkönen et al, 2014;Klefoth et al, 2013), while individuals with higher growth rates have been found to be more vulnerable to commercial netting (Biro and Post, 2008). It is important to note that, while previous work has independently examined the correlation of boldness (Wilson et al, 2011) as well as metabolic rate (Redpath et al, 2010) with angling vulnerability, no studies have taken an integrative approach to simultaneously examine the relative influence of behavior, metabolic rate and hormones in driving the likelihood of capture. Defining these relationships is of critical importance in determining which characteristics may be under selective pressure, and what types of evolutionary alterations we can expect to see in populations exploited by recreational anglers.…”
Section: Introductionmentioning
confidence: 99%